Application of Unpleasant Symptoms Theory Assessment and Roy Adaptation Model Theory in Patients with Stage III Cervical Cancer - Ruth Jamlaay; Windy Natasha; Restuning Widiasih; Mira Trisyani (GLOBAL HEALTH SCIENCE GROUP, 2024)
Cervical cancer is a significant global health problem, with the number of cases and deaths rising every year. Patients with cervical cancer often experience symptoms such as bleeding, vaginal discharge, and pain, which significantly affect their quality of life. The aim of this study to conduct a comprehensive assessment, including physical, psychological, and social aspects, in managing patients with cervical cancer cannot be ignored. In patient management, in-depth evaluation of physiological factors such as bleeding, hydronephrosis, and electrolyte imbalance, as well as psychological and social factors, is essential to reduce the risk of morbidity and mortality. Nursing theories, such as Theory of Unpleasant Symptoms (TOUS) and Roy's Adaptation Model, can be used to conduct a comprehensive assessment and provide optimal care to cervical cancer patients. Social support also plays an important role in helping patients and their families adapt to the changes faced due to this disease. With a holistic and collaborative approach, it is hoped that morbidity and mortality rates for cervical cancer patients can be reduced both globally and in Indonesia.